Reconstructing the Original New Testament: A Critical Analysis of Bart D. Ehrman's Arguments on Textual Errors and Manuscript Transmission (Journal of Comparative Study of Religions, 2023)
This study aimed to discuss the thought of Bart D. Ehrman, an American New Testament Scholar, regarding this idea of the contradiction in his research into the New Testament in many of his books, which was considered controversial and initiated a heated debate among theologians and other scholars. This research employed a library research method by analyzing various written sources such as books, articles, and scientific journals that discuss Bart D. Ehrman's thoughts on the contradictions in the New Testament. The nature of this research is qualitative, where the researcher analyzes and interprets textual data to understand Ehrman's thoughts and their implications for New Testament studies. Ehrman affirmed that since its initial copying process, the Bible had been using the hand-copying method, resulting in many errors in the manuscript. Up to the number of copyists who copy back the wrong copy and make new mistakes; eventually, many copies of the New Testament exist today, but none of these copies are known to be copies of the original book, nor copies of the first copies. Instead, they are copies of copies of other copies that have been scattered long after the original writing period. Which undoubtedly contains very many errors and differences in each copy. Mistakes that arise because they are intentional or unintentional. This study concluded that, according to Ehrman, it has been very tough to reconstruct the original text of the New Testament. Nevertheless, even so, he still stated that it was a big mistake deciding to stop learning the texts of the New Testament.